Screen reading: electromagnetic information leakage from the computer monitor - Grdović, Milena M.; Protić, Danijela D.; Antić, Vladimir D.; Jovanović, Boriša Ž. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The security of systems can be jeopardized by compromising emanations. This paper provides an overview of computer screen attacks. New technologies can be used to exfiltrate sensitive data from computer screens. Emission security is the prevention of electromagnetic signal attacks that are conducted or radiated.Methods: This paper examines the impact of a side-channel attack that intercepts compromised information from a computer screen. The leakage of electromagnetic data is also explained. Software-defined radios are described to explain malicious attacks on computer monitors.Results: The source of the electromagnetic signal determines the nature of the side-channel information they carry. The most well-known issue associated with revealing emissions is the possibility of intercepting visual information displayed on computer monitors. Conclusion: Visual data displayed on computer monitors could be intercepted by a software-defined radio which can digitize the desired frequency spectrum directly from an antenna, present it to a digital signal processor, and output it to an application for revealing sensitive data. A variety of countermeasures, such as shielding, zoning, soft TEMPEST, and similar techniques, can be used to prevent data leakage.
Keywords: electromagnetic emission; information leakage; computer monitor